Nice teams finish last the secret to unleashing your team's maximum potential - Miller, Brian Cole 1956- (American Management Association, 2010)
Don't rock the boat. Don't make waves. Don't offend anyone. There's a palpable feeling that clouds many team meetings and keeps them from being productive: over-politeness. And while the conflict that naturally exists in most organizations hasn't gone away, it manifests itself in passive-aggression, mediocrity, and a molasses-like inability to get anything done. Nice Teams Finish Last provides the antidote to this all-too-common tendency, giving managers, team leaders and members, and facilitators the practical support they need to battle "the nice trap" and start getting results! The book hel
Includes bibliographical references and index. - Print version record
Keywords: Teams in the workplace; Communication in organizations; Interpersonal communication; Équipes de travail; Communication dans les organisations; Communication interpersonnelle; BUSINESS & ECONOMICS; Workplace Culture; BUSINESS & ECONOMICS; Corporate Governance; BUSINESS & ECONOMICS; Leadership; BUSINESS & ECONOMICS; Organizational Development